1917 Or. Gen. and Special Laws 804, ch. 377, § 1 - (:unkn) unknown (My University, 1917)
No person shall carry in any city, town, or municipal corporation of this State any pistol, revolver or other firearm concealed upon his or her person, or of a size which may be concealed upon his or her person, without a license or permit therefor, issued to him or her by a chief of police or sheriff of such city, town or municipal corporation, or in such manner as may be prescribed by ordinance of such city, town or municipal corporation. This section, however, shall not apply to sheriffs and their deputies, constables, marshals, police officers or any other duly appointed peace officers, nor to any person or persons summoned by such officers to assist in making arrest or preserving the peace while said person or persons are engaged in assisting such officers; nor to duly authorized military organizations when parading, nor to members thereof when going to and from places of meeting of their respective organizations.
Keywords: CARRY - CONCEALED